모래 3체 마모시험 장비(3-body abrasion tester)를 이용한 PLA프린팅 표면의 형상별 트라이볼로지 성능 분석 - 최용석(Yong Seok Choi); 박경렬(Kyeongryeol Park); 강성민(Seongmin Kang); 김운성(Unseong Kim); 정경은(Kyungeun Jeong); 박영진(Young Jin Park); 이경준(Kyungjun Lee) (Tribology and Lubricants, 2023)
This study applies various surface patterns to minimize material loss in construction equipment that is subject to severe wear due to sand, such as the wear-resistant steel plates of dump trucks or the teeth of excavators. The relationship between surface morphology and wear behavior is investigated using PLA+ polymer to observe the effect of the surface pattern. Five types of samples - smooth, concave, convex, wavy concave, and wavy convex designs - are created using a 3D printer. A wear experiment is conducted for a duration of 3 h using 6.5 kg of abrasive particles. The mass loss of the samples after the experiment is measured to assess the extent of wear. Additionally, the surface morphology of the samples before and after the experiment is analyzed using SEM and confocal microscopy. The study results reveal that the smooth design exhibits the highest wear loss, whereas the concave and wavy concave designs show relatively lower wear loss. The convex and wavy convex designs exhibit varying contact areas with the abrasive particles depending on the surface pattern, resulting in different levels of wear. Furthermore, a comparison between the experimental results and DEM simulations confirms the observed wear trends. This study reveals the relationship between wear damage according to surface pattern shape and is expected to be of substantial help in the analysis of wear and tear on agricultural and heavy equipment.